Konsep Akhlakul Karimah Perspektif Imam Al Ghazali - Syamsul Bahri (2022)
Akhlakul Karimah is a conscious ritual performed to recognize the positive character of each child. Such as the Islamic education system that was initiated by Imam Al-Ghazali, who emphasized the importance of recognizing the moral values that were built in accordance with the foundation of the Islamic education system. Considering how important morality is for children from birth, the main questions in this study are how to define morality according to Imam Al-Ghazali and how to use the pairing method. The method used in this research is library research. The key technique used in this research is descriptive analysis. Primary and secondary data were used as data sources, and comparative deductive methods were used for data analysis. According to the findings of the study, Imam Al-Ghazali advocated moral education through developing the character of children and teaching them commendable qualities from a young age, using mujahadah-riyadhah to form morals, and training themselves to develop the desired behavior, or karimah. Following up on these findings, the process of forming akhlaq karimah must be optimized through the family from an early age.